Lead paste for high rate valve regulated lead acid battery and method of making same
Patent Information
- Application Number
- CN202610035725.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-12
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-01-12
AI Technical Summary
然而,现有技术存在如下问题:其一,添加的短纤维仅能实现物理增强,亲酸性差,无法辅助硫酸吸附与快速迁移,孔隙率提升带来的储酸优势难以充分发挥;其二,单纯提升孔隙率易导致铅膏强度下降,增加短纤维的用量则会引发孔隙率下降等新问题,难以兼顾储酸能力、结构稳定性与导电性能的协同优化,无法适配高倍率放电对“硫酸快速迁移、电子高效传导、结构稳定抗脱落”的综合需求
(1)本发明通过对短纤维进行羧酸类单体与硅烷类单体复合改性,改性后的短纤维兼具亲酸储酸与硫酸传导功能,既能通过交织形成三维骨架强化铅膏结构稳定性,有效防止充放电循环中的铅膏脱落,又能通过表面羧基与硅氧烷基团吸附硫酸形成微储酸区,借助纤维网络加速硫酸迁移,解决高倍率放电时表层酸耗尽、内层酸迁移滞后的问题,充分发挥了铅膏孔隙的储酸优势。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of lead-acid batteries, and particularly to a lead paste for a high-rate valve-regulated lead-acid battery and its preparation method. Background Technology
[0002] Valve-regulated lead-acid (VRA) batteries are widely used in backup power applications requiring short-duration, high-current discharge, such as 15-minute, 10-minute, or 5-minute emergency backup power, due to their advantages such as being sealed and maintenance-free, having a compact structure, and controllable costs. The design principle of VRA batteries involves injecting the required amount of electrolyte into the plates and separators. With no free electrolyte, the oxygen absorption capacity is enhanced by the moisture properties of the negative plate. To prevent electrolyte loss, the battery must be sealed; therefore, it is also known as a "starved electrolyte battery."
[0003] In practical applications, high-rate discharge performance is a key indicator for this type of battery. According to the chemical reaction laws of batteries, the discharge process involves the reaction of sulfuric acid in the plates and separators. However, in existing technologies, when the battery discharges at a high current, the sulfuric acid on the surface of the plates is rapidly consumed, while the sulfuric acid inside the plates migrates slowly and cannot be replenished to the reaction interface in time. This causes the battery voltage to drop rapidly, prematurely terminating the discharge and making it difficult to meet the actual needs of short-term emergency backup power.
[0004] To address these issues, conventional industry solutions often involve optimizing the acid-to-water ratio in lead paste and adjusting its apparent density to increase porosity, thereby storing more sulfuric acid. Simultaneously, short fibers are added to the lead paste to enhance structural stability and prevent it from detaching during charging and discharging. However, existing technologies suffer from the following problems: First, the added short fibers only provide physical reinforcement and have poor acid affinity, failing to assist in sulfuric acid adsorption and rapid migration, thus hindering the full realization of the acid storage advantage brought by increased porosity. Second, simply increasing porosity can lead to a decrease in lead paste strength, while increasing the amount of short fibers can cause new problems such as further decreases in porosity. It is difficult to simultaneously optimize acid storage capacity, structural stability, and conductivity, and it cannot meet the comprehensive requirements of high-rate discharge for "rapid sulfuric acid migration, efficient electron conduction, and structural stability against detachment." Therefore, how to overcome the functional limitations of existing materials and solve core pain points such as slow sulfuric acid migration, high electrode internal resistance, and easy lead paste detachment during high-rate discharge without compromising the compatibility of existing production processes or significantly increasing costs has become an urgent problem to be solved in this field. Summary of the Invention
[0005] In view of the shortcomings of the prior art, the purpose of this invention is to provide a lead paste for valve-regulated lead-acid batteries that can balance sulfuric acid storage and rapid migration, structural stability and anti-shedding, low internal resistance and high conductivity, and its preparation method, in order to solve the above problems.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: A lead paste for a high-rate valve-regulated lead-acid battery and its preparation method, comprising positive electrode lead paste and negative electrode lead paste; The positive electrode lead paste comprises the following raw materials in parts by weight: 500 parts lead powder, 52-56 parts pure water, 51-53 parts dilute sulfuric acid, and 0.15-0.17 parts modified short fiber; The negative electrode lead paste comprises the following raw materials in parts by weight: 500 parts lead powder, 48-52 parts pure water, 35-37 parts dilute sulfuric acid, 0.15-0.17 parts modified short fiber, 5-7 parts barium sulfate, and 1-1.5 parts modified lignin. The modified short fiber is a short fiber modified with carboxylic acid monomers and silane monomers; the modified lignin is lignin modified with nano-conductive particles.
[0007] The lead paste for the high-rate valve-regulated lead-acid battery and its preparation method, wherein the modification process of the short fibers is as follows: cleaning the short fibers; dissolving carboxylic acid monomers and silane monomers in anhydrous ethanol by stirring, then adding an initiator and dispersing evenly to obtain a mixture; adding the short fibers and the mixture to a reaction vessel and reacting under heating and stirring conditions; after the reaction is completed, filtering to separate the short fibers, washing and drying to obtain modified short fibers.
[0008] The lead paste for the high-rate valve-regulated lead-acid battery and its preparation method, wherein the short fiber is one or more of polypropylene, polyester, and ethylene; the short fiber has a length of 0.8-1.0 mm and a diameter of 10-15 μm.
[0009] The lead paste for the high-rate valve-regulated lead-acid battery and its preparation method thereof, wherein the carboxylic acid monomer is one or more of maleic anhydride, fumaric acid, and itaconic acid; the silane monomer is one or more of vinyltriethoxysilane, vinyltrimethoxysilane, and γ-methacryloyloxypropyltrimethoxysilane; and the initiator is one or more of benzoyl peroxide, azobisisobutyronitrile, and a persulfate-sulfite composite system.
[0010] The lead paste for the high-rate valve-regulated lead-acid battery and its preparation method, wherein the mass ratio of the carboxylic acid monomer to anhydrous ethanol is (5-8):100, the mass ratio of the silane monomer to anhydrous ethanol is (4-9.6):100, and the amount of initiator added is 0.5-1.5% of the total mass of the carboxylic acid monomer and the silane monomer.
[0011] The lead paste for the high-rate valve-regulated lead-acid battery and its preparation method, wherein the modification process of the lignin is as follows: dissolving the dispersant in water and then adding nano-conductive particles, ultrasonically dispersing to form a suspension; adding lignin to the suspension, stirring evenly, and then drying to obtain modified lignin.
[0012] The lead paste for the high-rate valve-regulated lead-acid battery and its preparation method, wherein the lignin is in powder form with a particle size ≤100μm and a purity ≥85%.
[0013] The lead paste for the high-rate valve-regulated lead-acid battery and its preparation method thereof, wherein the dispersant is one or more of polyethylene glycol, polypropylene glycol, polyethylene glycol monomethyl ether, sodium dodecylbenzene sulfonate-polyoxyethylene sorbitan monooleate composite system, and sodium carboxymethyl cellulose; the amount of the dispersant added is 5-8% of the wood content.
[0014] The lead paste for the high-rate valve-regulated lead-acid battery and its preparation method, wherein the nano-conductive particles are graphene nanosheets or carbon nanotubes; the mass ratio of the nano-conductive particles to the lignin is 1:(10-15).
[0015] A method for preparing lead paste for high-rate valve-regulated lead-acid batteries includes the following steps: S1. Preparation of positive electrode lead paste: Add lead powder and modified short fibers to the paste mixing machine and stir; then add pure water and stir; then add dilute sulfuric acid and control the paste mixing temperature ≤65℃; after the acid is added, continue stirring to obtain positive electrode lead paste; S2. Preparation of negative electrode lead paste: Add lead powder, modified short fiber, modified lignin, and barium sulfate to a paste mixing machine and stir; then add pure water and stir; then add dilute sulfuric acid and control the paste mixing temperature to ≤65℃; after the acid is added, continue stirring to obtain negative electrode lead paste.
[0016] Beneficial effects: This invention provides a lead paste for a high-rate valve-regulated lead-acid battery and its preparation method, which has the following advantages: (1) This invention modifies short fibers by combining carboxylic acid monomers and silane monomers. The modified short fibers have both acid-loving and acid-storage functions and sulfuric acid conduction functions. They can strengthen the structural stability of lead paste by forming a three-dimensional skeleton through interweaving, effectively preventing lead paste from falling off during charge and discharge cycles. They can also adsorb sulfuric acid through surface carboxyl groups and siloxane groups to form micro acid storage areas. With the help of the fiber network, sulfuric acid migration is accelerated, solving the problem of surface acid depletion and inner acid migration lag during high-rate discharge, and giving full play to the acid storage advantage of lead paste pores.
[0017] (2) This invention modifies lignin with nano-conductive particles. While retaining the original lignin's ability to inhibit lead sulfate crystal aggregation and delay electrode passivation, the modified lignin constructs a continuous conductive network through uniformly distributed nano-conductive particles on its surface. This significantly reduces the internal resistance of the negative electrode plate and improves electron conduction efficiency, especially enhancing the high-rate discharge performance under low-temperature conditions, thus meeting the complex requirements of emergency backup power scenarios. Simultaneously, barium sulfate in the negative electrode lead paste synergistically with the modified lignin, further refining the lead sulfate crystals, maintaining the porous structure of sponge-like lead, and strengthening the anti-passivation effect and the stability of the lead paste.
[0018] (3) This invention optimizes the acid-water ratio of the positive and negative electrode lead pastes, complementing the functions of modified short fibers and modified lignin. While ensuring suitable porosity and apparent density of the lead paste, it avoids the impact on performance caused by simply adjusting porosity or the amount of additives. The components work synergistically in the system, achieving a simultaneous improvement in acid storage capacity, structural stability, conductivity, and low-temperature adaptability without increasing production costs or process complexity. Detailed Implementation
[0019] This invention provides a lead paste for a high-rate valve-regulated lead-acid battery and its preparation method. To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the following embodiments are provided to further illustrate the invention in detail. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the scope of protection of the invention.
[0020] This invention provides a lead paste for a high-rate valve-regulated lead-acid battery, comprising positive lead paste and negative lead paste.
[0021] The positive electrode lead paste, calculated by mass, comprises the following raw materials: 500 parts lead powder, 52-56 parts pure water, 51-53 parts dilute sulfuric acid, and 0.15-0.17 parts modified short fiber.
[0022] The negative electrode lead paste comprises the following raw materials in parts by weight: 500 parts lead powder, 48-52 parts pure water, 35-37 parts dilute sulfuric acid, 0.15-0.17 parts modified short fiber, 5-7 parts barium sulfate, and 1-1.5 parts modified lignin.
[0023] Specifically, the modified short fibers in the positive and negative electrode lead pastes are short fibers modified with carboxylic acid monomers and silane monomers. The modified lignin in the negative electrode lead paste is lignin modified with nano-conductive particles.
[0024] The short fibers used in the positive and negative electrode lead pastes, after being modified by carboxylic acid monomers and silane monomers, no longer only undertake a single physical reinforcement function, but also have the characteristics of acid affinity and acid storage and sulfuric acid conduction. They can prevent lead paste from falling off by forming a three-dimensional skeleton through interweaving, and can also form micro acid storage areas by adsorbing sulfuric acid through surface carboxyl groups and siloxane groups. Furthermore, they can accelerate sulfuric acid migration with the help of fiber networks, thus solving the problem of surface acid depletion and inner acid migration lag during high-rate discharge.
[0025] After the lignin in the negative electrode lead paste is modified by nano-conductive particles, it retains the original lignin's anti-passivation function and inhibits the aggregation of lead sulfate crystals, while adding the ability to build a conductive network. This effectively reduces the internal resistance of the negative electrode and improves the electronic conduction efficiency. Combined with the grain refinement and structural support of 5 to 7 parts of barium sulfate, the anti-passivation effect and the stability of the lead paste are further enhanced.
[0026] The acid-to-water ratio of the positive and negative electrodes complements the functions of the modified short fibers and modified lignin, ensuring that the lead paste has suitable porosity and apparent density. The components work synergistically within the system, ultimately achieving a synergistic leap in multiple properties without increasing additive costs or process burden, overcoming the difficulty in simultaneously achieving acid storage, reinforcement, and conductivity in existing technologies.
[0027] The modification process of the short fibers in this invention is as follows: (1) Fiber pretreatment: The short fibers are soaked in anhydrous ethanol for 12±0.5h to remove oil and impurities from the surface of the short fibers, so as to avoid impurities from hindering the subsequent grafting reaction. After being taken out, they are washed several times with pure water to remove residual anhydrous ethanol. Then, they are dried in an oven at 80℃ to constant weight to ensure that there is no moisture on the surface of the short fibers. Specifically, the short fibers are one or more of polypropylene, polyester, and ethylene; the length of the short fibers is 0.8~1.0mm and the diameter is 10~15μm. The above-mentioned performance of the short fibers can ensure the compatibility and dispersibility of the short fibers with the lead paste system, avoid agglomeration due to unsuitable materials or excessive size, and affect the uniformity of the lead paste. At the same time, they can form a dense three-dimensional skeleton through appropriate size, so as to realize the reinforcement of the lead paste structure, sulfuric acid adsorption and rapid conduction.
[0028] (2) Preparation of mixture: Dissolve carboxylic acid monomers and silane monomers in anhydrous ethanol by stirring, then add initiator, and ultrasonically disperse for 5 minutes until completely dissolved to form a stable reaction system.
[0029] Specifically, the carboxylic acid monomer is one or more of maleic anhydride, fumaric acid, and itaconic acid, added in an amount of 5-8 parts per 100 parts of anhydrous ethanol. All selected monomers contain unsaturated double bonds and carboxyl groups. The double bonds can undergo a grafting reaction with the surface of short fibers under the action of an initiator, while the carboxyl groups impart excellent acid affinity to the short fibers, enabling them to adsorb sulfuric acid. The above-mentioned dosage range ensures that the carboxyl group density on the surface of the grafted fiber is appropriate, avoiding both insufficient dosage leading to poor acid affinity and excessive dosage causing monomer waste or over-grafting resulting in agglomeration.
[0030] Specifically, the silane monomer is one or more of vinyltriethoxysilane, vinyltrimethoxysilane, and γ-methacryloyloxypropyltrimethoxysilane, added in an amount of 4–9.6 parts per 100 parts of anhydrous ethanol. The vinyl groups in the selected silane monomer can synergistically graft with carboxylic acid monomers. The silanol groups formed after hydrolysis of the siloxane groups can enhance the interfacial bonding between the modified layer and the short fibers and the active material of the lead paste, improving structural stability. The dosage is compatible with that of the carboxylic acid monomers, ensuring the function of the modified short fibers.
[0031] Specifically, the initiator is one or more of benzoyl peroxide, azobisisobutyronitrile, and a persulfate-sulfite composite system, and the amount added is 0.5% to 1.5% of the total mass of the carboxylic acid monomers and silane monomers. The initiator needs to decompose efficiently at the set reaction temperature to generate free radicals and initiate the synergistic graft polymerization of the two monomers. The above-mentioned dosage range, measured according to the total mass of the two types of monomers, can ensure the initiation efficiency and avoid insufficient grafting due to insufficient initiator, or side reactions due to excessive initiation affecting the modification effect.
[0032] (3) Grafting: The pretreated short fibers and the mixture are added to the reactor and stirred at 70-80℃ and 100-200 r / min for 3-4 h. The above reaction conditions are adapted to the decomposition rate of the initiator and the reactivity of the monomers. This allows the initiator to decompose efficiently to generate free radicals, which initiates the grafting polymerization of the two monomers on the surface of the short fibers, forming a composite modified layer containing carboxyl and siloxane groups. Stirring also ensures that the short fibers and the mixture are in full contact, achieving uniform grafting and avoiding insufficient local modification.
[0033] (4) Post-processing: After the reaction is complete, the short fibers are separated by filtration and washed multiple times with anhydrous ethanol to remove ungrafted free monomers and residual initiators, preventing them from entering the lead paste and affecting the electrochemical performance of the battery. The filtrate is then washed with pure water until the pH is neutral to thoroughly remove residual impurities and avoid interference from acidic or alkaline substances on the lead paste reaction. The fibers are then dried in a vacuum oven at 60°C until constant weight to obtain the modified short fibers.
[0034] The modification process of lignin in this invention is as follows: (1) Pre-dispersion of nano-conductive particles: Dissolve the dispersant in pure water, add the nano-conductive particles, and ultrasonically disperse for 15-20 min to form a stable suspension. Specifically, the dispersant is one or more of polyethylene glycol, polypropylene glycol, polyethylene glycol monomethyl ether, sodium dodecylbenzene sulfonate-polyoxyethylene sorbitan monooleate composite system, and sodium carboxymethyl cellulose, and the amount added is 5-8% of the lignin mass. The above dispersant can encapsulate the particle surface through steric hindrance or charge repulsion effect, destroying the aggregation tendency of graphene nanosheets or carbon nanotubes. At the same time, the amount used matches the composite requirements of lignin and nano-conductive particles, avoiding both insufficient dispersant leading to aggregation of nano-conductive particles and excessive residue affecting the electrochemical performance of lead paste. The nano-conductive particles are graphene nanosheets or carbon nanotubes, and their mass ratio with lignin is 1:(10-15). The nano-conductive particles possess excellent conductivity and can construct a continuous conductive network on the surface of lignin. The aforementioned mass ratio ensures that the nano-conductive particles are uniformly attached to the surface and pores of lignin, thus preserving the original anti-passivation function of lignin in inhibiting the aggregation of lead sulfate crystals while imparting conductive properties.
[0035] (2) Lignin composite mixture: Lignin is added to the suspension and stirred at a high speed of 250-300 r / min for 30 minutes. The purpose is to ensure that the lignin and the nano-conductive particles are in full contact and firmly bonded. The shear force generated by high-speed stirring promotes the uniform adhesion of the nano-particles in the suspension to the lignin surface and pores. The high specific surface area of lignin provides stable attachment sites for the nano-conductive particles. Specifically, the lignin is in powder form with a particle size ≤100μm and a purity ≥85%. This limitation is to improve the compatibility between lignin and nano-conductive particles, ensure the uniformity of the composite, and avoid impurities or large lignin particles affecting the composite effect.
[0036] (3) Drying and Shaping: The lignin composite mixture from step (2) is fed into a spray dryer, with the inlet air temperature controlled at 110-120℃ and the outlet air temperature at 50-60℃. After drying, powdered modified lignin is obtained. Spray drying allows the lignin composite mixture to be rapidly atomized into small droplets, which are then quickly dehydrated in the high-temperature airflow, preventing secondary agglomeration of the nano-conductive particles during the drying process, ultimately resulting in powdered modified lignin. By controlling the inlet and outlet air temperatures, sufficient moisture removal is ensured, while avoiding high-temperature damage to the chemical structure of lignin and the conductivity of the nano-conductive particles.
[0037] This invention provides a method for preparing lead paste for high-rate valve-regulated lead-acid batteries, comprising the following steps: (1) Preparation of positive electrode lead paste: Add lead powder and modified short fibers to a paste mixing machine and stir; then add pure water, and continue stirring for 6-8 minutes after the water is added; then add dilute sulfuric acid, and control the acid addition time within 5-9 minutes, and the paste temperature ≤65℃; after the acid is added, continue stirring for 11-14 minutes to obtain an apparent density of 3.9-4.1 g / cm³. 3 Positive lead paste.
[0038] (2) Preparation of negative electrode lead paste: Add lead powder, modified short fiber, modified lignin, and barium sulfate to a paste mixing machine and stir; then add pure water, and continue stirring for 6-8 minutes after the water is added; then add dilute sulfuric acid, controlling the acid addition time within 5-9 minutes, and the paste temperature ≤65℃; after the acid is added, continue stirring for 11-14 minutes to obtain an apparent density of 4.3-4.5 g / cm³. 3 Negative electrode lead paste.
[0039] The lead powder in both the positive and negative electrode lead pastes has an oxidation degree of 70-80% and a particle size of 1-5 μm. The density of the dilute sulfuric acid is d = 1.400 g / cm³. 3 The conductivity of pure water is ≤1 μS / cm. The particle size of barium sulfate in the negative electrode lead paste is 50–80 nm.
[0040] This invention provides a high-rate valve-regulated lead-acid battery, comprising positive electrode lead paste and negative electrode lead paste; both the positive and negative electrode lead pastes are assembled after coating, curing, and drying; the coating process parameters are: coating pressure 0.15–0.2 MPa, coating speed 6–7 m / min, and coating thickness 2.1–3.1 mm. This limitation ensures that the lead paste containing modified short fibers and modified lignin can adhere uniformly to the grid, avoiding uneven internal reactions due to excessive coating thickness or insufficient capacity due to excessively thin coating, while also adapting to the viscosity characteristics of the modified lead paste to ensure consistent plate forming; the precise coating thickness also reserves suitable space for sulfuric acid storage and ion conduction, matching the acid storage and conductivity functions of the modified components. The curing and drying process parameters are: curing at 45–50°C and 80–85% humidity for 10–12 hours, followed by drying at 60°C for 6–7 hours. The curing stage allows the active materials in the lead paste to fully react and form a stable structure, strengthening the interfacial bonding between the modified short fibers and the active materials in the lead paste and preventing them from falling off during subsequent charging and discharging. The drying stage gradually removes excess moisture, ensuring the stability of the lead paste porosity and preventing residual moisture from affecting the electrochemical performance of the battery. At the same time, it avoids high temperatures from damaging the conductive network of the modified lignin and the anti-passivation structure of the lignin.
[0041] To further illustrate the lead paste for a high-rate valve-regulated lead-acid battery and its preparation method provided by the present invention, the following examples and comparative examples are provided.
[0042] Example 1 I. Preparation of modified short fibers: (1) Raw materials: 20 parts polypropylene short fiber, 6 parts maleic anhydride (MAH) (purity ≥99%), 5 parts vinyltriethoxysilane (VTES) (purity ≥98%), 0.055 parts benzoyl peroxide (BPO) (0.5% of the total mass of monomers), 100 parts anhydrous ethanol (purity ≥99.5%), and 30 parts deionized water (conductivity ≤0.8μs / cm).
[0043] (2) Fiber pretreatment: Soak polypropylene short fibers in anhydrous ethanol for 12 hours, take them out and wash them 3 times with deionized water, and dry them in an 80℃ oven for 2 hours until constant weight. (3) Preparation of mixture: Add MAH and VTES to anhydrous ethanol and stir to dissolve. Then add BPO and disperse with a 150W ultrasonic device for 5 minutes until completely dissolved. (4) Grafting reaction: Add the pretreated short fibers to the reactor, pour in the above mixture, seal and heat to 75°C, stir at 100 r / min for 3.5 h; (5) Post-treatment: After the reaction is completed, the short fibers are separated by filtration, washed twice with anhydrous ethanol, and then washed with deionized water until the pH of the filtrate is 7. The filtrate is then placed in a vacuum oven at 60°C and dried for 3 hours until constant weight is obtained to obtain modified short fibers.
[0044] II. Preparation of modified lignin: (1) Raw materials: 10 parts of lignin (particle size ≤100μm, purity ≥85%), 0.8 parts of graphene nanosheets (particle size 5~10nm), 0.6 parts of polyethylene glycol (PEG-6000) (molecular weight 6000), and 100 parts of deionized water (conductivity ≤0.8μs / cm).
[0045] (2) Graphene pre-dispersion: PEG-6000 was added to deionized water and stirred to dissolve. Then graphene nanosheets were added and dispersed for 20 minutes using a 150W ultrasonic device to prepare a stable suspension (suspension stability ≥24h).
[0046] (3) Lignin composite mixing: Add lignin to the above suspension and stir at a high speed of 300 r / min for 30 minutes.
[0047] (4) Drying and molding: The mixture is fed into a spray dryer, and the inlet air temperature is controlled at 120°C and the outlet air temperature is controlled at 60°C. After drying, powdered modified lignin is obtained.
[0048] III. Preparation of positive electrode lead paste: Add 500 parts lead powder and 0.165 parts modified short fiber to the paste mixing machine and stir; then add 54 parts pure water, and continue stirring for 7 minutes after the water is added; then add 52.5 parts dilute sulfuric acid, and control the acid addition time within 6 minutes, and the paste mixing temperature ≤65℃; after the acid is added, continue stirring for 12 minutes to obtain positive electrode lead paste.
[0049] IV. Preparation of negative electrode lead paste: Add 500 parts lead powder, 0.165 parts modified short fiber, 1.3 parts modified lignin, and 6.5 parts barium sulfate to a paste mixing machine and stir. Then add 50 parts pure water and continue stirring for 6-8 minutes after the water is added. Then add 36.5 parts dilute sulfuric acid, controlling the acid addition time within 6 minutes, and keep the paste mixing temperature ≤65℃. After the acid is added, continue stirring for 13 minutes to obtain negative electrode lead paste.
[0050] Example 2 The raw materials used to prepare the modified short fiber are: 20 parts of a composite product of polypropylene and polyester in a mass ratio of 1:1, 6 parts of fumaric acid, 5 parts of vinyltrimethoxysilane (VTMS), 0.055 parts of a sodium persulfate-sodium sulfite composite system (0.5% of the total mass of monomers), 100 parts of anhydrous ethanol (purity ≥99.5%), and 30 parts of deionized water (conductivity ≤0.8μs / cm). Other components are the same as in Example 1.
[0051] Example 3 The raw materials for preparing modified lignin are: 10 parts lignin (particle size ≤ 100 μm, purity ≥ 85%), 1 part carbon nanotubes (particle size 5-10 nm), 0.7 parts polyethylene glycol monomethyl ether, and 100 parts deionized water (conductivity ≤ 0.8 μs / cm). Other components are the same as in Example 1.
[0052] Comparative Example 1 Unmodified short fibers and modified lignin (same as in Example 1) were added as raw materials for lead paste, and other aspects were the same as in Example 1.
[0053] Comparative Example 2 When modifying the short fibers, no silane monomer (vinyltriethoxysilane) was added, and the rest was the same as in Example 1.
[0054] Comparative Example 3 When modifying the short fibers, the amount of carboxylic acid monomer (maleic anhydride) added was 12 parts, and the rest was the same as in Example 1.
[0055] Comparative Example 4 When modifying the short fibers, no carboxylic acid monomers (maleic anhydride) were added, and the rest was the same as in Example 1.
[0056] Comparative Example 5 When modifying the short fibers, the amount of silane monomer (vinyltriethoxysilane) added was 12 parts, and the rest was the same as in Example 1.
[0057] Comparative Example 6 Unmodified lignin was used as the raw material for lead paste, and other procedures were the same as in Example 1.
[0058] Performance testing 1. Porosity of the positive electrode plate: The lead pastes from Examples 1-3 and Comparative Examples 1-6 were used to make positive electrode plates of the same thickness, wherein the grid size (length × width × thickness) was 125 × 134 × 2.5 mm and the coating thickness was 3.1 mm. The porosity and acid storage volume of each positive electrode plate are shown in Table 1.
[0059] Table 1. Test results of porosity of positive electrode plate
[0060] 2. Porosity of the negative electrode plate: The lead pastes from Examples 1-3 and Comparative Examples 1-6 were used to make negative electrode plates of the same thickness, with grid dimensions (length × width × thickness) of 125 × 134 × 1.8 mm and coating thickness of 2.1 mm. The porosity and acid storage volume of each negative electrode plate are shown in Table 2.
[0061] Table 2 Test results of negative electrode porosity
[0062] 3. 15-Minute Constant Power Test of the Battery: Batteries were assembled using plates of the same thickness and number of plates. Each cell contained 15 positive plates and 16 negative plates. A 15-minute constant power discharge test was conducted according to the standard YD / T3427-2018, "High-Rate Valve-Regulated Sealed Lead-Acid Batteries for Communication Use". The discharge power was 800W / cell, and the termination voltage was 1.67V / cell. Each battery sample was tested four times, and the average value was taken. The results are shown in Table 3.
[0063] Table 3. Test results of the battery at constant power for 15 minutes.
[0064] 4. Battery power density coefficient test: According to the standard YD / T3427-2018 "High-rate valve-regulated sealed lead-acid batteries for communication", the actual test battery power density coefficient Kp = constant power value for 15 minutes / measured 10-hour rate capacity. The larger the power density coefficient Kp, the better the high-rate discharge performance of the battery and the higher the cost performance. The test results are shown in Table 4.
[0065] Table 4 Test Results of Battery Power Density Coefficient
[0066] Examples 1-3 were prepared using the scheme of this invention to prepare lead paste and assembled into batteries. All performance test results showed excellent performance and strong stability. Regarding plate porosity and acid storage capacity, the porosity and acid storage volume of the positive / negative electrode lead pastes in Examples 1-3 were significantly higher than those in the comparative examples, demonstrating the synergistic effect of the modified short fibers' acid-loving and acid-storage function and optimized acid-to-water ratio. In terms of high-rate discharge performance, all three batteries achieved a 15-minute constant power discharge time far exceeding the standard requirement of 15 minutes; the 10-hour rate capacity, 15-minute constant power value, and power density coefficient Kp exhibited excellent high-rate discharge power output and overall cost-effectiveness. In terms of cycle stability and low-temperature performance, the lead paste shedding rate of Examples 1-3 after 500 charge-discharge cycles was only 0.05% to 0.06%, the internal resistance of the negative electrode plate at 25°C was as low as 5.9mΩ to 6.2mΩ, and the discharge capacity retention rate at low temperature (-10°C) was as high as 94.5% or more. This indicates that the structural reinforcement effect of modified short fibers and the conductive and passivation prevention function of modified lignin form an effective synergy, taking into account structural stability, conductivity and low-temperature adaptability.
[0067] Comparative Example 1, due to the addition of ordinary short fibers, resulted in the lead paste lacking acid affinity and storage capacity, only providing physical reinforcement. It could not assist in the migration of sulfuric acid, and its interfacial bonding with the active material of the lead paste was weak, leading to a simultaneous decline in acid storage capacity, structural stability, and high-rate discharge performance.
[0068] In Comparative Example 2, the lack of silane monomer modification resulted in insufficient interfacial bonding of the modified short fibers, reduced synergy between structural reinforcement and acid-loving and acid-storing functions, and affected the stability of lead paste and sulfuric acid migration efficiency.
[0069] In Comparative Example 3, the addition of excessive carboxylic acid monomers led to over-grafting of some short fibers, resulting in agglomeration, which reduced the porosity of the lead paste and affected the formation of conductive pathways, causing a decrease in acid storage capacity and conductivity.
[0070] Comparative Example 4 lacks carboxylic acid monomers, resulting in insufficient acid affinity of the short fibers, which cannot effectively adsorb and conduct sulfuric acid, and also affects the structural reinforcement effect of the grafted modified layer, leading to poor high-rate discharge performance and stability.
[0071] In Comparative Example 5, the excessive silane monomers caused the modified layer to thicken, blocking some of the lead paste pores. Although the interfacial bonding strength was improved, the acid storage space was reduced. This balanced the structural stability and acid storage capacity, but the overall performance was not as good as the example.
[0072] Comparative Example 6 did not modify the lignin, so the lead paste could only achieve the function of preventing passivation, but had no conductive properties. This led to a surge in the internal resistance of the negative electrode, obstructed electron conduction, a significant decrease in reaction efficiency at high discharge rates, and the inability to form a synergy with the modified short fibers, which greatly affected the structural stability and overall performance of the lead paste.
[0073] It is understood that those skilled in the art can make equivalent substitutions or changes to the technical solution and inventive concept of the present invention, and all such changes or substitutions should fall within the protection scope of the present invention.
Claims
1. A lead paste for a high-rate valve-regulated lead-acid battery, characterized in that, Including positive electrode lead paste and negative electrode lead paste; The positive electrode lead paste comprises the following raw materials in parts by weight: 500 parts lead powder, 52-56 parts pure water, 51-53 parts dilute sulfuric acid, and 0.15-0.17 parts modified short fiber; The negative electrode lead paste comprises the following raw materials in parts by weight: 500 parts lead powder, 48-52 parts pure water, 35-37 parts dilute sulfuric acid, 0.15-0.17 parts modified short fiber, 5-7 parts barium sulfate, and 1-1.5 parts modified lignin. The modified short fiber is a short fiber modified with carboxylic acid monomers and silane monomers; the modified lignin is lignin modified with nano-conductive particles. The modification process of the short fibers is as follows: The short fibers are washed; carboxylic acid monomers and silane monomers are dissolved in anhydrous ethanol by stirring, then an initiator is added and dispersed evenly to obtain a mixture; the short fibers and the mixture are added to a reaction vessel and reacted under heating and stirring conditions; after the reaction is completed, the short fibers are separated by filtration, washed, and dried to obtain modified short fibers; the carboxylic acid monomers are one or more of maleic anhydride, fumaric acid, and itaconic acid; the silane monomers are one or more of vinyltriethoxysilane, vinyltrimethoxysilane, and γ-methacryloyloxypropyltrimethoxysilane. The modification process of the lignin is as follows: the dispersant is dissolved in water and then the nano-conductive particles are added and ultrasonically dispersed to form a suspension; the lignin is added to the suspension, stirred evenly, and then dried to obtain modified lignin; the dispersant is one or more of polyethylene glycol, polypropylene glycol, polyethylene glycol monomethyl ether, sodium dodecylbenzenesulfonate-polyoxyethylene sorbitan monooleate composite system, and sodium carboxymethyl cellulose; the nano-conductive particles are graphene nanosheets or carbon nanotubes.
2. The lead paste for a high-rate valve-regulated lead-acid battery according to claim 1, characterized in that, The short fiber is one or more of polypropylene, polyester, and ethylene; the short fiber has a length of 0.8 to 1.0 mm and a diameter of 10 to 15 μm.
3. The lead paste for a high-rate valve-regulated lead-acid battery according to claim 1, characterized in that, The initiator is one or more of benzoyl peroxide, azobisisobutyronitrile, and persulfate-sulfite composite systems.
4. The lead paste for a high-rate valve-regulated lead-acid battery according to claim 1, characterized in that, The mass ratio of the carboxylic acid monomer to anhydrous ethanol is (5-8):100, the mass ratio of the silane monomer to anhydrous ethanol is (4-9.6):100, and the amount of initiator added is 0.5-1.5% of the total mass of the carboxylic acid monomer and the silane monomer.
5. The lead paste for a high-rate valve-regulated lead-acid battery according to claim 1, characterized in that, The lignin is in powder form with a particle size ≤100μm and a purity ≥85%.
6. The lead paste for a high-rate valve-regulated lead-acid battery according to claim 1, characterized in that, The amount of dispersant added is 5-8% of the wood content.
7. The lead paste for a high-rate valve-regulated lead-acid battery according to claim 1, characterized in that, The mass ratio of the nano-conductive particles to the lignin is 1:(10-15).
8. A method for preparing lead paste for a high-rate valve-regulated lead-acid battery as described in any one of claims 1-7, characterized in that, Includes the following steps: S1. Preparation of positive electrode lead paste: Add lead powder and modified short fibers to the paste mixing machine and stir; then add pure water and stir; then add dilute sulfuric acid and control the paste mixing temperature ≤65℃; after the acid is added, continue stirring to obtain positive electrode lead paste; S2. Preparation of negative electrode lead paste: Add lead powder, modified short fiber, modified lignin, and barium sulfate to a paste mixing machine and stir; then add pure water and stir; then add dilute sulfuric acid and control the paste mixing temperature to ≤65℃; after the acid is added, continue stirring to obtain negative electrode lead paste.
Citation Information
Patent Citations
Negative lead paste for lead-acid storage battery and preparation method thereof
CN110729461A
Lead plaster formula of long-life valve-regulated lead-acid storage battery and preparation method thereof
CN112736248A
Lead-acid storage battery negative electrode lead paste and preparation method thereof
CN112768676A